OC-007 A Multicenter, Double-Blind, Placebo (PBO)-Controlled Ph3 Study of Ustekinumab (UST), AHuman MAB to IL-12/23P40, IN PTS with Moderately-Severely Active Crohn's Disease (CD) Who are Naïve or not Refractory to anti-TNFΑ: UNITI-2. (17th August 2016) - Feagan, B; Gasink, C; Lang, Y; Friedman, JR; Johanns, J; Gao, L-L; Sands, B; Hanauer, S; Rutgeerts, P; Targan, S; Ghosh, S; de Villiers, W; et al.
Abstract : Introduction: In the Ph2b CERTIFI study, a single intravenous (IV) UST induction dose was effective & safe in CD pts previously failing anti-TNFs, 1 but efficacy in pts only failing conventional therapy is unknown. We evaluated 2 IV UST induction dose regimens in a CD population not refractory to anti-TNFs. Methods: Pts with moderate-severely active CD (CDAI 220–450) who failed conventional therapy but were not refractory to anti-TNFs were randomised to a single dose of IV PBO, UST 130 mg, or weight-based tiered UST dosing ~6  mg/kg. Primary endpoint was clinical response at Wk6 (reduction in CDAI score of ≥100 pts). At Wk8, pts transitioned to IM-UNITI maintenance study or had safety follow-up through Wk20. Results: Of 628 pts randomised, median disease duration was 6.4 yrs; baseline (BL) mean CDAI was 303; 39% & 35% were receiving steroids & immunomodulators, respectively at BL; 69% were naïve to anti-TNFs. At Wk6, 55.5% & 51.7% in ~6 mg/kg & 130 mg UST grps were in clinical response vs 28.7% PBO (p < 0.001). At Wk8, 40.2% & 30.6% of pts in ~6 mg/kg & 130 mg UST grps were in clinical remission vs 19.6% PBO (p ≤ 0.009). Both UST doses showed significant improvements vs PBO in CDAI, IBDQ, CRP, & faecal lactoferrin & calprotectin. Proportions of AEs, SAEs, & infections were similar in UST & PBO grps. No malignancies, deaths, opportunistic infections or TB occurred in UST-treated pts. Conclusion: IV UST induced clinical response & remission in pts with moderate-severe CD not previously failing anti-TNFs & was well-tolerated through induction. Reference: 1 Sandborn WJ, et al . N Engl J Med 2012;367 :1519–1528. Disclosure of Interest: B. Feagan Grant/research support from: Abbott/AbbVie, Amgen, Astra Zeneca, Bristol-Myers Squibb (BMS), Janssen Biotech (Centocor), JnJ/Janssen, Roche/Genentech, Millennium, Pfizer, Receptos, Santarus, Sanofi, Tillotts, UCB Pharma, Consultant for: Abbott/AbbVie, Actogenix, Akros, Albireo Pharma, Amgen, Astra Zeneca, Avaxia Biologics Inc., Avir Pharma, Axcan, Baxter Healthcare Corp., Biogen Idec, Boehringer-Ingelheim, Bristol-Myers Squibb, Calypso Biotech, Celgene, Elan/Biogen, EnGene, Ferring Pharma, Roche/Genentech, GiCare Pharma, Gilead, Given Imaging Inc., GSK, Ironwood Pharma, Janssen Biotech (Centocor), JnJ/Janssen, Kyowa Kakko Kirin Co Ltd., Lexicon, Lilly, Lycera BioTech, Merck, Mesoblast Pharma, Millennium, Nektar, Nestles, Novonordisk, Pfizer, Prometheus Therapeutics and Diagnostics, Protagonist, Receptos, Salix Pharma, Serono, Shire, Sigmoid Pharma, Synergy Pharma Inc., Takeda, Teva Pharma, TiGenix, Tillotts, UCB Pharma, Vertex Pharma, VHsquared Ltd., Warner-Chilcott, Wyeth, Zealand, Zyngenia, Speaker bureau with: Abbott/AbbVie, JnJ/Janssen, Takeda, Warner-Chilcott, UCB Pharma, Conflict with: Patent holder; Member Scientific Advisory board, Abbott/AbbVie, Amgen, Astra Zeneca, Avaxia Biologics Inc., Bristol-Myers Squibb, Celgene, Centocor Inc., Elan/Biogen, Ferring, JnJ/Janssen, Merck, Nestles, Novartis, Novonordisk, Pfizer, Prometheus Laboratories, Protagonist, Salix Pharma, Takeda, Teva, TiGenix, Tillotts Pharma AG, UCB Pharma; Member, Board of Directors Officer – Robarts Clinical Trials Inc, C. Gasink Shareholder of: Janssen, Employee of: Janssen, Y. Lang Shareholder of: Janssen, Employee of: Janssen, J. Friedman Shareholder of: Janssen, Employee of: Janssen, J. Johanns Shareholder of: Janssen, Employee of: Janssen, L.-L. Gao Shareholder of: Janssen, Employee of: Janssen, B. Sands Grant/research support from: Janssen, Consultant for: Janssen, S. Hanauer Grant/research support from: Janssen, Consultant for: Janssen, Conflict with: Lecturer for Janssen, P. Rutgeerts Grant/research support from: J&J, Merck, UCB, AbbVie, Consultant for: J&J, Merck, UCB, AbbVie, Millenium/Takeda, Genentech/Hoffman LaRoche, Medimmune/AstraZeneca/Amgen, Merck/Serono, Bristol Myers Squibb, Robarts, Tillotts Pharma, Conflict with: Lectures for J&J, Merck, AbbVie, S. Targan Grant/research support from: Cedars-Sinai Medical Centre, Consultant for: Janssen, NuMedii, Inc., Conflict with: Advisory board for the Seaver Foundation; Scientific Advisory Board Member Symbiotix, S. Ghosh Grant/research support from: Abbvie, Conflict with: International Steering Committees: Janssen, Abbvie, Pfizer, Receptos, BMS, Aerpio; Advisory Committees: Takeda, Abbvie, Janssen, Pfizer, Allergan, W. de Villiers Conflict with: member of steering committee, active participant as investigator, J.-F. Colombel Consultant for: Pfizer, Takeda, Protagonist Therapies, Celgene, Genentech, Second Genome, Vertex, Amgen, Merck Sharp Dohme, Janssen, Nestle, AbbVie, Tigenix, Receptos, Conflict with: Speaker for AbbVie, Ferring, Shire, Takeda, Z. Tulassay: None Declared, U. Seidler Conflict with: Local continuing medical education seminars for MSD, W. Sandborn Grant/research support from: Receptos, Exact Sciences, Amgen, the American College of Gastroenterology, Broad Foundation, Prometheus Laboratories, AbbVie, Boehringer Ingelheim, Takeda, Atlantic Pharmaceuticals, Janssen, Bristol-Myers Squibb, Genentech, Pfizer, and Nutrition Science Partners, Conflict with: Personal fees from Receptos, Prometheus Laboratories, AbbVie, Boehringer Ingelheim, Takeda, Atlantic Pharmaceuticals, Janssen, Bristol-Myers Squibb, Genentech, Pfizer, Nutrition Science Partners, Kyowa Hakko Kirin, Millennium Pharmaceuticals, Celgene Cellular Therapeutics, Santarus, Salix Pharmaceuticals, Catabasis Pharmaceuticals, Vertex Pharmaceuticals, Warner Chilcott, Gilead Sciences, Cosmo Pharmaceuticals, Ferring Pharmaceuticals, Sigmoid Biotechnologies, Tillotts Pharma, Am Pharma BV, Dr. August Wolff, Avaxia Biologics, Zyngenia, Ironwood Pharmaceuticals, Index Pharmaceuticals, Nestle, Lexicon Pharmaceuticals, UCB Pharma, Orexigen, Luitpold Pharmaceuticals, Baxter Healthcare, Ferring Research Institute, Amgen, Novo Nordisk, Mesoblast Inc., Shire, Ardelyx Inc., Actavis, Seattle Genetics, MedImmune (AstraZeneca), Actogenix NV, Lipid Therapeutics Gmbh, Eisai, Qu Biologics, Toray Industries Inc., Teva Pharmaceuticals, Eli Lilly, Chiasma, TiGenix, Adherion Therapeutics, Immune Pharmaceuticals, Celgene, Arena Pharmaceuticals, Ambrx Inc., Akros Pharma, Vascular Biogenics, Theradiag, Forward Pharma, Regeneron, Galapagos, Seres Health, Ritter Pharmaceuticals, Theravance, Palatin, Biogen, and the University of Western Ontario (owner of Robarts Clinical Trials); non-financial support from Receptos